Understanding long-term continence rates after robot-assisted laparoscopic prostatectomy – one-year follow-up on “Cognitive ability as a non-modifiable risk factor for post-prostatectomy urinary incontinence” - Reichert, Mathias; Ploeger, Hannah Maria; Uhlig, Annemarie; Strauss, Arne; Henniges, Philipp; Trojan, Lutz; Mohr, Mirjam Naomi (Frontiers in Surgery, 2022)
Purpose: To evaluate long-term continence rates (12 months) in patients after robot-assisted laparoscopic prostatectomy (RALP) in relation to their cognitive ability (CoAb), which proved to be a predictor for early post-prostatectomy incontinence. Material & Methods: This is the 12-month follow-up evaluation of our previously published observational single-center, prospective evaluation of 84 patients who underwent RALP as treatment of their localized prostate cancer between 07/2020 and 03/2021. Post-prostatectomy incontinence (PPI) was measured by asking patients about their 24 h pad usage, whereby 0 pads were considered continent and ≥1 pad was considered incontinent. CoAb was evaluated by performing the Mini-Mental State Examination prior to surgery. Possible predictors for PPI were evaluated using univariate and multivariable logistic regression models. Results: Multivariable logistic regression analyses identified early incontinence status and nerve sparing (NS) as independent predictors for PPI after 12 months, resulting in a 5.69 times higher risk of PPI when the loss of urine was between 10-50 ml during the early performed pad test (one day after catheter removal) compared to 0-1 ml loss of urine (95% confidence interval (CI): 1.33-28.30, p=0.024) and a 6.77 times higher risk for PPI, respectively, when only unilateral NS was performed compared to bilateral NS (95% CI: 1.79-30.89, p=0.007). CoAb lost its predictive value for long-term PPI (p=0.44). Conclusion: The results of this study suggest that PPI is a dynamic, rather than a static condition with a dynamically changing pathophysiology within the first 12 months after RALP. Coping methods and therapies should adapt to this circumstance.